2004
DOI: 10.1001/archopht.122.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-up Study of Blood-Retinal Barrier and Retinal ThicknessAlterations in Patients With Type 2 Diabetes Mellitus and Mild NonproliferativeDiabetic Retinopathy

Abstract: To examine the 3-year alterations of the blood-retinal barrier and changes in retinal thickness occurring in the macular region in 14 eyes of 14 patients with type 2 diabetes mellitus (DM) and mild nonproliferative diabetic retinopathy. Methods:We classified 14 eyes of 14 patients with type 2 DM and mild nonproliferative diabetic retinopathy, as having disease levels 20 (microaneurysms only) or 35 (microaneurysm plus retinal hemorrhage[s] and/or hard exudates) of Wisconsin Card-Sorting Test grading, by using 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The results described herein may have a major impact on the management of diabetic retinopathy, particularly if the studies of Klein et al [4], using simple microaneurysm counts, and Lobo et al [23], using determination of microaneurysm turnover, are confirmed in a larger number of patients for a longer follow-up period. The results of this study showed that by using the method described it is possible to reliably identify microaneurysm turnover by calculating microaneurysm formation and disappearance rates and, therefore, activity of the retinopathy in its early stages.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The results described herein may have a major impact on the management of diabetic retinopathy, particularly if the studies of Klein et al [4], using simple microaneurysm counts, and Lobo et al [23], using determination of microaneurysm turnover, are confirmed in a larger number of patients for a longer follow-up period. The results of this study showed that by using the method described it is possible to reliably identify microaneurysm turnover by calculating microaneurysm formation and disappearance rates and, therefore, activity of the retinopathy in its early stages.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, computer-assisted determination of microaneurysm turnover in these same eyes and at the same intervals clearly showed a progressive increase in the number of new microaneurysms. This increase was different in different eyes with the same level of retinopathy, potentially identifying eyes in which the retinal disease is more active and possibly progressing more rapidly [23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is the fact that the ETDRS classification was constructed on the basis that DR, given time, uniformly progresses to proliferative retinopathy. It is now apparent, from the data available from a variety of longitudinal studies and from clinical experience, that the evolution and progression of DR varies between different individuals and does not necessarily progress in every patient to the terminal stage of proliferative retinopathy [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Developments based on high-speed confocal scanning laser ophthalmoscopy brought new insights into the onset and progression of DR from its earliest to its most advanced stages [152,153,154,155,156,157,158]. …”
Section: Other Imaging Modalitiesmentioning
confidence: 99%